Naturally Derived Anti-HIV Polysaccharide Peptide (PSP) Triggers a Toll-Like Receptor 4-Dependent Antiviral Immune Response - Madeline Rodríguez-Valentín; Sheila López; Mariela Rivera; Eddy Ríos-Olivares; Luis Cubano; Nawal M. Boukli (Journal of Immunology Research, 2018)
Aim. Intense interest remains in the identification of compounds to reduce human immunodeficiency virus type 1 (HIV-1) replication. Coriolus versicolor’s polysaccharide peptide (PSP) has been demonstrated to possess immunomodulatory properties with the ability to activate an innate immune response through Toll-like receptor 4 (TLR4) showing insignificant toxicity. This study sought to determine the potential use of PSP as an anti-HIV agent and whether its antiviral immune response was TLR4 dependent. Materials and Methods. HIV-1 p24 and anti-HIV chemokine release was assessed in HIV-positive (HIV+) THP1 cells and validated in HIV+ peripheral blood mononuclear cells (PBMCs), to determine PSP antiviral activity. The involvement of TLR4 activation in PSP anti-HIV activity was evaluated by inhibition. Results. PSP showed a promising potential as an anti-HIV agent, by downregulating viral replication and promoting the upregulation of specific antiviral chemokines (RANTES, MIP-1α/β, and SDF-1α) known to block HIV-1 coreceptors in THP1 cells and human PBMCs. PSP produced a 61% viral inhibition after PSP treatment in HIV-1-infected THP1 cells. Additionally, PSP upregulated the expression of TLR4 and TLR4 inhibition led to countereffects in chemokine expression and HIV-1 replication. Conclusion. Taken together, these findings put forward the first evidence that PSP exerts an anti-HIV activity mediated by TLR4 and key antiviral chemokines. Elucidating these new molecular mediators may reveal additional drug targets and open novel therapeutic avenues for HIV-1 infection.